Evaluation of toluene transformation in an Extractive Membrane Bioreactor (EMBR) - Loh, Aron Shu Tien (Nanyang Technological University, 2020)
This thesis presents the findings of a lab-scale microaerobic Extractive Membrane Bioreactor (EMBR) on toluene treatment under oxygen limiting condition (no aeration). A comparison study was carried out between fabricated 4wt% ZIF-8@PDMS/PVDF membrane and commercial PDMS membrane, in terms of overall flux performance and biofilm formation. This membrane bioreactor utilizes a non-porous membrane as a barrier between the wastewater and the biological growth medium. The membrane extracts the targeted organic compounds from the wastewater feed and transport into the opposite side of the aqueous bio medium, which allows biodegradation to take place without exposing to the hostile composition of the wastewater. The lab-scale microaerobic EMBR’s maximum toluene elimination capacity per effective membrane area was found to be 1.18 and 1.34 g/m2 hour on the commercial and synthetic membrane, respectively. The synthetic membrane was found to outperform the commercial membrane throughout the experiment. The commercial PMDS membrane with 100 μm thickness shows a mass transfer coefficient, of 2.6 ± 0.6× 10-5 m/s. Similarly, a 4wt% ZIF-8@PDMS/PVDF membrane with an average thickness of 13.7 ± 0.7 μm shows a mass transfer coefficient, of 3.4 ± 0.3 × 10-5 m/s. As the experiment progress, the growth of the biofilm on the membrane surface formed a layer of resistance which reduces the mass transfer of toluene. The formation of biofilm reduced the overall mass transfer by 60~70%, and signs of decreasing toluene removal efficiency were noted after operation for 17 days. Thus, cleaning was conducted to recover the mass transfer performance, and it was operated for another 17 days again. Based on the microbial community results, Zoogloea and Acidovorax were found to the main toluene degraders in the system. The feasibility of operating the EMBR in a low energy and operation cost is possible, by eliminating the need for aeration and using mixed culture.